Pembingkaian Berita Penghapusan Presidential Threshold pada Media Online Kompas.Com dan CNNIndonesia - Nabila Safira Azizah; Christabella, Fionna (UIN Raden Mas Said Surakarta, 2025)
This study investigates how Kompas.com and CNN Indonesia frame news coverage of the abolition of the Presidential Threshold by applying Robert N. Entman’s bingkai analysis model. Employing a qualitative descriptive design with textual analysis as the core method, the research examines six news articles—three from each outlet—selected to represent the respective editorial and reporting styles. The analysis operates at the message level, focusing on media texts as sites of ideological construction in the context of constitutional discourse. Findings reveal that Kompas.com predominantly emphasizes legal-formal dimensions and institutional stability, whereas CNNIndonesia foregrounds critical responses from academics and civil society concerning the broader implications of the policy.